2012
DOI: 10.4314/ajtcam.v9i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes in male accessory reproductive organs in rats exposed to cigarette smoke and the protective effect of honey supplementation

Abstract: The effect of cigarette smoke (CS) on histology of male accessory reproductive organs and the possible protective effect of honey supplementation in rats were investigated in this study. Rats received distilled water, honey, CS exposure or honey plus CS exposure. Honey (1.2 g/kg body weight/day) was administered by gavage and CS exposure (3 times per day) was done in a chamber for 13 weeks. CS exposure significantly increased relative weight of epididymis and ventral prostate. There were also significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In Chinese traditional medicine, the seeds of this plant have been prescribed as a tonic for stomach disorders, and the whole aerial part of the plant is used as a folk medicine for the treatment of renal diseases in the Northern-East region of China. Many phytochemical studies on constituents of the seeds have been reported 5 . The name fenugreek comes from foenum-graecum, meaning Greek hay, as the plant was traditionally used to scent inferior hay 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese traditional medicine, the seeds of this plant have been prescribed as a tonic for stomach disorders, and the whole aerial part of the plant is used as a folk medicine for the treatment of renal diseases in the Northern-East region of China. Many phytochemical studies on constituents of the seeds have been reported 5 . The name fenugreek comes from foenum-graecum, meaning Greek hay, as the plant was traditionally used to scent inferior hay 6 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, a lot of research has been done to study the role of different natural products in male reproductive functions (Mohamed et al, 2011;Mohamed et al, 2012;Mohamed et al, 2013). Some studies have used whole plant extracts, thus taking advantage of the abundance of different phytochemicals which have several intervention targets, while others have used specific compounds isolated from plants.…”
Section: Introductionmentioning
confidence: 99%